ANALISIS KOMUNIKASI INFLUENCER MARKETING DALAM PENGGUNAAN FITUR LIVE PADA APLIKASI TIKTOK - Jentayu; Sori Monang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Indonesia's TikTok application is currently responding to a huge demand for creativity and business from the community. There are now several influencers in the marketing industry who use live features to run their businesses with their own linguistic style and personal branding. A linguistic style is someone's use of the richness of a language when speaking or writing. Moreover, certain types of use can also be interpreted to achieve particular effects or general characteristics of the language of the literary group. The purpose of this study was to analyze the influencer's marketing communication methods for getting customer's attention through the live TikTok feature in doing business. This research method uses the AIDA theory (Awareness, Interest, Desire, Action). The results of this study came from the TikTok account @ddhivaaaaa. This study aims not only to increase knowledge, but also to provide information on the use of language-style his TikTok application in influencer marketing, especially in live events.